A CLINICO-MYCOLOGICAL EVALUATION OF DERMATOPHYTIC INFECTIONS – A SINGLE CENTRE PROSPECTIVE OBSERVATIONAL STUDY - SIDDIQUI, SABA MOHSIN; PHULARI, YOGANAND J; HIREMATH, RAVISHEKAR N; PATIL, CHETAN; PATEL, PRIYANKA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Background: The epidemiology of dermatophytic infection is influenced by the changing patterns of migration, growth in tourism, immunocompetence of the host, pathogenicity of the infectious agents, availability of medical treatment, and changes in socioeconomic conditions. Objectives: The objectives of the study were to assess the epidemiological profile, clinical types, and association between the etiological agent isolated and the clinical type of dermatophytic infections. Methods: An observational prospective study was carried out at large tertiary care hospital in Southern Maharashtra, India. 110 Participants were selected based on Inclusion and exclusion criteria. Data collection was done with help of personal interview and detailed examination by investigator using predesigned, pre-tested, and structured questionnaire. All patients were followed up in dermatology department till complete investigation, treatment, and discharge. Results: Patients belonging to 21−40 year constituted 45% of the study population. Male to female ratio was 3:1. About 51.82% belonged to low socio-economic status and 56.36% were from rural areas. The most common isolate obtained was Trichophyton rubrum (25.45%) followed by Trichophyton mentagrophytes (7.27%). Out of the 110 samples collected, 66.36% (73 samples) were KOH positive and 35.45% (39 samples) were culture positive. The most common type of mixed dermatophytic infection was Tinea Corporis with Tinea Cruris (38.46%) followed by Tinea Manuum with Tinea Unguium (30.77%). Mixed type was seen more commonly in 21−40 years age group (30.77%). Association of isolate and the clinical type involved among study participants was assessed by applying Chi-square test which showed no statistical significance (p=0.94). Similarly, association of results of KOH mount and culture report to clinical types also showed no statistical significance (p=0.94). However, when association of age and sex with clinical types was assessed, age showed statistically significant association (p=0.004) while sex showed no statistical significance (p=0.32). Conclusions: Incidence of dermatophytosis was maximum in rural areas, low socioeconomic group and in summer. Thus, changing environmental and socio-economic conditions often led to changing epidemiology of dermatophytic infections. Tinea corporis was found to be the commonest clinical type followed by Tinea cruris. T. rubrum was the commonest isolate obtained (25.45%). Fungi were demonstrated by direct microscopy and/or by culture in 73 cases (66.36%) out of 110 cases. Hence, direct microscopy with or without culture is an important diagnostic tool in dermatophytosis. Authors recommend more in-depth study with larger sample size and multicentric based to have clearer picture of dermatophytosis.